Evaluation of neuropsychological outcome and "quality of life" after glioma surgery - Wolf, Julia; Campos, Benito; Bruckner, Thomas; Vogt, Lidia; Unterberg, Andreas; Ahmadi, Rezvan (Langenbeck's archives of surgery, 2016)
Extended tumour resection is imperative to improve the outcome of glioma patients but also carries the risk of increasing morbidity and thus, potentially, of decreasing the patient’s quality of life (QOL). In this pilot study, we evaluated how postoperative neurological and neuropsychological alterations impacted on QOL in patients who underwent glioma resection.